SHORELINE CHANGES IN THUA THIEN-HUE LAGOON SYSTEM - Trinh, Le Phuoc (Vietnam Journal of Marine Science and Technology, 2014)
In southern Thua Thien Hue province, a long and narrow sandy coast (barrier islands) splits water inside lagoons from outside, Gulf of Tonkin. Shoreline is impacted directly by waves, so it often causes robust changes in northeast monsoon, which could influence local people and economy significantly. In this study, the results showed that Thuan An inlet moved toward northwest, the extreme (weather) phenomena made the inlet open/closure repeatedly, and so on. From the results, we can classify into two basic types of shoreline changes: one is movement of Thuan An inlet; the other is topographic change in barrier islands. Their lytho-hydrodynamic processes have opposite directions, contrasting magnitudes on power and time. The impact of two characteristics in northeast monsoon was analyzed particularly as reasons: one was chaotic waves in front of Gulf of Tonkin; the other was wave field from enhanced NE monsoon spells. Comparing the results of two cases near shore, angle of wave ray deflected oppositely, magnitudes of wave power and time were different. Mechanism of wave impact in the extreme case (opening/closure inlet), unstable dynamic status of barrier islands were studied as well.